Lifelong learning : education across the lifespan - Field, John, 1949-; Leicester, Mal (Routledge, 2000)
'Lifelong Learning' is a hot issue for educators across the world, as societies everywhere are concerned with developing a literate, skilled and flexible workforce and to widen participation in education at all levels and for all age-groups. This book covers all the major issues, with well-known academic contributors working in the field and covering the topics of theoretical, global and curriculum perspectives, widening participation and the industrial university. Topics covered include:* Community education* Popular education* Higher education* The corporate unive.